PROBLEMATIKA PENGGABUNGAN DAERAH - Tryatmoko, Mardyanto Wahyu (Pusat Penelitian Politik, 2011)
The implementation of regional government splitting or proliferation in Indonesia has created many acuteproblems in the local level Meanwhile amalgamation of local government as clearly stated in the regulationis considered as being impossible implemented by the central government itself Government is concerned thatamalgamation policy will only bring turmoil in the region This study explores both society s understanding andgovernment s strategy regarding the possibility of local government amalgamation in Indonesia This study alsomaps both driving and inhibiting factors of the amalgamation policy implementation in Indonesia This studyshows that both elite and people in the study areas do not have an understanding ofconcepts about the benefits ofamalgamation as an alternative policy of regional arrangement